2020
DOI: 10.1159/000505207
|View full text |Cite
|
Sign up to set email alerts
|

Association between Adult Attention Deficit/Hyperactivity Disorder and Intravenous Misuse of Opioid and Benzodiazepine in Patients under Opioid Maintenance Treatment: A Cross-Sectional Multicentre Study

Abstract: Background: Intravenous misuse and attention-deficit/hyperactivity disorder (ADHD) are common in patients under opioid maintenance treatment (OMT), who often misuse benzodiazepine (BZD). Objectives: To explore the rate of adult ADHD among patients under OMT in Italy and whether screening positive for adult ADHD is associated with OMT and BZD misuse and emergency room (ER) admission because of misuse. Methods: We recruited 1,649 patients from 27 addiction units (AUs) in Italy and collected data on the self-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 52 publications
1
18
1
Order By: Relevance
“…The prevalence of adult ADHD symptoms in our sample was 8-12 times that in the general population (i.e., 2.5-5%) [13,14], and in accordance with previous studies in SUD patients [17][18][19][20][21]. The prevalence of patients positive to adult ADHD screening in this study was slightly higher than that in our previous report from a similar population and using the same screening test (31.7%) [27], probably because of the differences between the 2 populations, including the larger number of men, which are reported to be more prone to ADHD [32], in the present report.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The prevalence of adult ADHD symptoms in our sample was 8-12 times that in the general population (i.e., 2.5-5%) [13,14], and in accordance with previous studies in SUD patients [17][18][19][20][21]. The prevalence of patients positive to adult ADHD screening in this study was slightly higher than that in our previous report from a similar population and using the same screening test (31.7%) [27], probably because of the differences between the 2 populations, including the larger number of men, which are reported to be more prone to ADHD [32], in the present report.…”
Section: Discussionsupporting
confidence: 93%
“…This finding survived correction for potential covariates, in that ADHD was the factor that, together with age, influenced all QoL measures in the multivariate analysis. Despite the prevalence of adult ADHD is known to be higher in SUD patients than the general population [17][18][19][20][21], studies on the Here are reported only covariates that turned out to be significant in the multivariate linear regression analysis. Please note that higher SF-36 scores indicate higher QoL, while higher GHQ-12 scores indicate worse QoL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence estimates may differ according to the type of substance used and the subpopulations or treatment modality. For example, the following populations of patients in opioid maintenance treatment (OMT) were screened positively for ADHD: in Norway, 33% of OMT patients [5], in Austria, in 50% of children and 17% of adults of the mainly male prison inmates in OMT [6], and in Italy, 11.2% of OMT patients [7]. In the methamphetamine-using population of one hospital’s psychiatric center, the prevalence of the ADHD diagnosis went up to 55.6% [8].…”
Section: Introductionmentioning
confidence: 99%